2020
DOI: 10.7150/jca.40604
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB modulated miR-194-5p/IGF1R/PPFIBP axis is crucial for the tumorigenesis of ovarian cancer

Abstract: miRNAs are involved in the tumorigenesis of various malignancies. In the current study, we found that miR-194-5p expression is downregulated in ovarian cancer tissues, and downregulation of miR-194-5p expression promotes proliferation, invasion and migration of human ovarian cancer cells in vitro and ovarian tumor growth in nude mice. We further found that IGF1R and PPFIBP are targets of miR-194-5p, and downregulation of miR-194-5p expression increases IGF1R and PPFIBP expression, resulting in increased prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…As shown in previous studies, miR-194-5p acted as a tumor suppressor in many cancers, such as ovarian cancer 28 , bladder cancer 29 , glioblastoma multiforme 30 . Consistent with the aforementioned literature, miR-194-5p exerts an inhibitory effect in CRC.…”
Section: Discussionsupporting
confidence: 60%
“…As shown in previous studies, miR-194-5p acted as a tumor suppressor in many cancers, such as ovarian cancer 28 , bladder cancer 29 , glioblastoma multiforme 30 . Consistent with the aforementioned literature, miR-194-5p exerts an inhibitory effect in CRC.…”
Section: Discussionsupporting
confidence: 60%
“…Zheng et al (46) showed that YTHDF3 as an m 1 A reader decreased invasion and migration of trophoblast by inhibiting IGF1R expression. IGF1R was also reported as an oncogene in cancers (47). So, we speculated that YTHDF3 may regulate the expression of some oncogenes in CHOL.…”
Section: Discussionmentioning
confidence: 85%
“…The reduced expression of miR-194-5p promotes IGF1R and PPFIBP expression, promoting OC progression. NF-κB binds to the miR-194-5p promoter and negatively regulates miR-194-5p expression [ 53 ]. TPM1 overexpression has been demonstrated to promote cell apoptosis, inhibit migration, and its expression is correlated to OSCC prognosis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of MMP-1 in osteosarcoma cells contribute to cancer progression, metastasis, and stem-like properties [ 35 ]. In addition, a recent study has demonstrated that PPFIBP1 contributes to the tumorigenesis of OC [ 53 ]. MMP1 and PPIFIB1 expression have decreased with increasing drug time exposure that indicates MMP1 and PPIFIB1 expression might be associated with carboplatin sensitivity.…”
Section: Discussionmentioning
confidence: 99%